Beta-lactam-azasugar hybrid as a competitive potent galactosidase inhibitor - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M.; Puranik, Vedavati G. (Tetrahedron Letters, 2006)
A beta-lactam-azasugar hybrid (polyhydroxylated carbacephem) has been designed and synthesized as a potent glycosidase inhibitor. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: beta-Galactosidase; beta-lactam-azasugar; glycosidase inhibitor; hybrid molecules

Binding of T-antigen disaccharides to artocarpus hirsuta lectin and jacalin are energetically different - Gaikwad, Sushama M.; Khan, Mohammad Islam (Photochemistry and Photobiology, 2006)
The thermodynamics of binding of Me-alpha-GalNAc, Gal-beta-1-3GalNAc-alpha-O-Me (T-antigen-alpha), Gal-beta-1-3GalNAc and Gal-alpha-1-6Glc (mellibiose) to Artocarpus hirsuta lectin was studied using fluorescence spectroscopy. The binding affinities of the saccharides are in the order Gal-beta-1-3GalNAc-alpha-O-Me > Me-alpha-GalNAc > Me-alpha-Gal > Gal-beta-1-3GalNAc > Gal-alpha-1-6Glc. The binding affinities were comparable to those for jacalin. However, binding of the saccharides to the A. hirsuta lectin was not affected as strongly by temperature as observed in jacalin and the trend was found to be reversed. Values for Delta H and Delta S were found to be positive in A. hirsuta lectin-disaccharide binding despite similar binding affinities. Thus, with 99% structural and 96% sequence homology, with similar sugar specificity and affinity, the energetics of the disaccharide binding of the two lectins seem to be different. Me-alpha-GalNAc binding to A. hirsuta lectin is enthalpically driven, because the association constant decreases with increasing temperature. However, the binding of the T-antigen disaccharides and mellibiose disaccharides to the lectin is entropically driven. The difference in the molecular associations in the packing and variation of the C-terminal length of the P chain of the A. hirsuta lectin could be reflected in the different disaccharide binding energetics.